KEKUATAN HUKUM AKTA KUASA SUBSTITUSI TERHADAP KEPEMILIKAN HAK ATAS TANAH BERDASARKAN AKTA PERJANJIAN JUAL BELI - Efendi, Deni; Nurdin, Zefrizal; Rosari, Anton (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2025)
In the sale and purchase agreement between Munir Datuk Rajo Intan as the seller and Cuaca Usmanto as the buyer, a transaction for land with Ownership Certificate Number 516/Sungai Sapih, covering 78,920 m², was made. The buyer has fully paid Rp.27,622,000. The practice includes granting a power of sale with substitution rights, allowing the power to be transferred to another party. However, the use of a power of attorney with substitution rights is prohibited under the Minister of Home Affairs Instruction No. 14 of 1982. This study aims to answer three main questions: 1) What is the legal force of the Deed of Power of Substitution in land ownership? 2) What is the position of the Sale and Purchase Agreement Act against third parties? 3) What is the process of changing the name of the certificate based on the Sale and Purchase Agreement Deed? The study uses a normative juridical approach with case and statute approaches. The findings show that a power of sale with substitution to avoid tax payment is invalid, as it does not align with the principle of consensus between the parties involved. To resolve this, it is recommended to cancel the Deed of Power of Attorney for Sale Substitution and carry out the name change through the proper procedure.